Budd-Chiari syndrome and heparin-induced thrombocytopenia in polycythemia vera: Successful treatment with repeated TIPS and interferon alpha - Farhat, Hussein (2009)
Polycythemia vera (PV) is a common cause of Budd-Chiari syndrome (BCS) and portal vein thrombosis (PVT). The postpartum period is a precipitating cofactor. An additional heparin-induced thrombocytopenia/thrombosis (HIT/T) leads to a life-threatening condition in which transjugular intrahepatic portosystemic shunting (TIPS) seems to be the only life-saving procedure. We describe the case of a subacute BCS and PVT in the late postpartum period. The diagnosis was established using CT scan, MRI, and Doppler ultrasonography of abdominal vessels and the laboratory findings were compatible with PV. After a successful creation of TIPS, a HIT/T worsened the hemorrhagic and thrombotic picture. TIPS procedure was successfully repeated and heparin was replaced with Fondaparinux and then vitamin K antagonist. The treatment with interferon alpha-2A, started after the normalization of liver functions, resulted in a complete remission within 6 months. The JAK2 V617F mutation clone remained undetectable after 2 years' follow-up.